Digital Leadership di Era Multieduhealthtainment 5.0 : Transformasi Peningkatan Mutu Pendidikan di Madrasah - Harry Soeratin; Asep Irfan Fanani (Peneliti.net, 2023)
This research is motivated by the importance of digital leadership skills that must be possessed by Madrasah Principals in the era of multieduhealthtainment 5.0. The development of the Multieduhealthcare 5.0 era is a new era with synergy between aspects of education, health aspects and aspects of entertainment marked by digital technology which is increasingly accelerating its development day by day. Of course, the changes in this era will also experience a transformation in the aspect of education, especially in improving the quality of education. The purpose of this paper is to describe 3 aspects namely 1) Digital Leadership in the Multieduhealthtainment 5.0 era; 2) Quality of Education in the Multieduhealthtainment 5.0 era; and 3) The role of Digital Leadership in transforming the quality of education in the Multieduhealthtainment 5.0 era. The method used in this research is Descriptive Qualitative Method with the focus of the main study, namely library research . The discussion from this study resulted in the conclusion that Digital Leadership is the ability possessed by a leader in using digital assets to make decisions quickly and precisely. Improving the Quality of Education in the Multieduhealthtainment 5.0 era. has two aspects, namely 1) Human Resources Aspect; 2) Content aspect/Curriculum Transformation. Furthermore, in order to improve the quality of education, Digital Leadership has several roles, namely the Head of School/Madrasah acts as 1) Visionary; 2) Conveners; 3) Team Sponsors; 4) Managers; 5) Innovators; and as Mentors. Not only that, other roles of Digital Leadership are: 1) building the Organization; 2) Integrate and take advantage of technology trends ; and 3) Develop an understanding of human resources.